EFFECT OF VITAMIN C AND COMBINATION OF VITAMIN C WITH PHYSICAL EXERCISE ON THE PAIN OF DYSMENORRHEA - Mondal, Satabdi; Ghosh, Badshah (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Dysmenorrhea is a common problem in adolescent girls and women; with moderate to severe pain, often refrain from their daily activity and also affect their profession and quality of life. In this study effect of vitamin C and vitamin C in combination with exercise on the pain of dysmenorrhea was examined on twenty girl students of age range 18-22 years suffering from the symptoms of mild to moderate primary dysmenorrhea. Pain was measured as Pain Rating Index (PRI) using McGill pain Questionnaire. Duration of the intervention was for consecutive 8 weeks and pain score was measured three times; before intervention, after 1st menstrual cycle and after second menstrual cycle. Results showed that pain score decreased after both the treatments. It was also observed that vitamin C in combination with exercise showed a better effect than vitamin C alone (P < 0.05).